2018
DOI: 10.3390/ma11050742
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Powder Characteristics on Processability of AlSi12 Alloy Fabricated by Selective Laser Melting

Abstract: Selective laser melting (SLM) is one of the additive manufacturing technologies that allows for the production of parts with complex shapes from either powder feedstock or from wires. Aluminum alloys have a great potential for use in SLM especially in automotive and aerospace fields. This paper studies the influence of starting powder characteristics on the processability of SLM fabricated AlSi12 alloy. Three different batches of gas atomized powders from different manufacturers were processed by SLM. The powd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(55 citation statements)
references
References 52 publications
1
54
0
Order By: Relevance
“…Yang et al reported their results on Cu-12.5Zn-2.9Si silicon brass alloy, in which Si is helpful to form the cellular structure by precipitation of the κ-Cu7Si phase [ 144 ]. Such a fine microstructure is ascribed to the high cooling rate during SLM and will be explained in detail below [ 129 , 145 , 146 ]. The microstructure of SLM Al-Si alloys changes significantly with the Si content.…”
Section: Microstructurementioning
confidence: 99%
“…Yang et al reported their results on Cu-12.5Zn-2.9Si silicon brass alloy, in which Si is helpful to form the cellular structure by precipitation of the κ-Cu7Si phase [ 144 ]. Such a fine microstructure is ascribed to the high cooling rate during SLM and will be explained in detail below [ 129 , 145 , 146 ]. The microstructure of SLM Al-Si alloys changes significantly with the Si content.…”
Section: Microstructurementioning
confidence: 99%
“…These areas of research have not so far received attention and require further research to clarify what the limits of achievable microstructures, mechanical properties, and physical properties are. The effects of the characteristics of the powder material [ 41 ] and build direction [ 42 , 43 ] on the AM process and the properties of the resulting materials need to be thoroughly investigated as well.…”
Section: Materials For Ammentioning
confidence: 99%
“…Among many AM‐based techniques, powder bed fusion methods such as selective laser melting (SLM) and electron beam melting (EBM) are the most popular choices for fabrication of metallic materials . SLM covers a wide range of metallic compositions including Al‐/Fe‐/Ti‐/Ni‐/Co‐/Cu‐based alloys and more, which has increased its popularity and demand for manufacturing metal‐based materials, outperforming the EBM . A systematic optimization of process parameters such as laser power, hatch style, scan speed, layer thickness and hatch distance during the SLM results in near‐dense products with superior mechanical and functional (magnetic/electrochemical/electronic) properties …”
Section: Introductionmentioning
confidence: 99%